2012
DOI: 10.1097/iae.0b013e31822d3a34
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Visual Outcome in Endogenous Candida Endophthalmitis

Abstract: Candida endophthalmitis is associated with a high rate of visual loss, particularly in patients with poor presenting visual acuity or centrally located lesions. Early vitrectomy reduces the risk of retinal detachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 27 publications
2
77
0
2
Order By: Relevance
“…Acute symptoms are often initially floaters (mobile obscuration of vision), redness, and discomfort of the eye followed by visual loss. Visual impairment may result from retinal detachment, vitreous infiltration, central chorioretinal lesions (22), and/or cataract formation (23). Endogenous endophthalmitis is a particular threat to quality of life because of its propensity to cause bilateral visual loss.…”
Section: Discussionmentioning
confidence: 99%
“…Acute symptoms are often initially floaters (mobile obscuration of vision), redness, and discomfort of the eye followed by visual loss. Visual impairment may result from retinal detachment, vitreous infiltration, central chorioretinal lesions (22), and/or cataract formation (23). Endogenous endophthalmitis is a particular threat to quality of life because of its propensity to cause bilateral visual loss.…”
Section: Discussionmentioning
confidence: 99%
“…11 More recently, an early vitrectomy has been associated with a significantly reduced risk of retinal detachment in eyes with Candida FEE; a retrospective review of 44 eyes with Candida FEE found a retinal detachment in 2 of 26 eyes receiving vitrectomy within a week compared with 7 of 17 eyes that did not receive a vitrectomy. 6 Technical advancements in vitrectomy, such as improved visualization through wide angle viewing and smaller gauge instruments, may be responsible for better reported visual outcomes in recent retrospective reports. 12 Vitrectomy can also improve the diagnosis of endogenous endophthalmitis, which often has an indolent course and nonspecific inflammatory symptoms, and thus can be misdiagnosed in 16% to 50% of cases.…”
Section: Discussionmentioning
confidence: 96%
“…4 Alternatively, vitrectomy may have a therapeutic effect by removing infectious organisms, clearing inflammatory molecules, and increasing intraocular penetration of systemic therapy 1,5 and may actually reduce the risk of retinal detachment. 6 Because of lack of prospective trials, the role of vitrectomy in FEE is uncertain. It is unclear if vitrectomy should be 1) performed at the time FEE is suspected, 2) reserved for severe cases of FEE, or 3) used in cases refractory to medical management.…”
mentioning
confidence: 99%
“…Patients with severe endophthalmitis or vitreitis should undergo surgical intervention [25]. The two main factors associated with a poor visual outcome are centrally located fungal lesions, and an initial poor visual acuity on presentation [26]. Prevention of endophthalmitis may be possible with early use of azoles.…”
Section: Discussionmentioning
confidence: 99%